Congenital heart diseases and cardiovascular abnormalities in 22q11.2 deletion syndrome: From well‐established knowledge to new frontiers. Issue 10 (16th April 2018) - Unolt, Marta; Versacci, Paolo; Anaclerio, Silvia; Lambiase, Caterina; Calcagni, Giulio; Trezzi, Matteo; Carotti, Adriano; Crowley, Terrence Blaine; Zackai, Elaine H.; Goldmuntz, Elizabeth; Gaynor, James William; Digilio, Maria Cristina; et al.
Abstract : Congenital heart diseases (CHDs) and cardiovascular abnormalities are one of the pillars of clinical diagnosis of 22q11.2 deletion syndrome (22q11.2DS) and still represent the main cause of mortality in the affected children. In the past 30 years, much progress has been made in describing the anatomical patterns of CHD, in improving their diagnosis, medical treatment, and surgical procedures for these conditions, as well as in understanding the underlying genetic and developmental mechanisms. However, further studies are still needed to better determine the true prevalence of CHDs in 22q11.2DS, including data from prenatal studies and on the adult population, to further clarify the genetic mechanisms behind the high variability of phenotypic expression of 22q11.2DS, and to fully understand the mechanism responsible for the increased postoperative morbidity and for the premature death of these patients. Moreover, the increased life expectancy of persons with 22q11.2DS allowed the expansion of the adult population that poses new challenges for clinicians such as acquired cardiovascular problems and complexity related to multisystemic comorbidity. In this review, we provide a comprehensive review of the existing literature about 22q11.2DS in order to summarize the knowledge gained in the past years of clinical experience and research, as well as to identify the remaining gaps in comprehension of this syndrome and the possible future research directions.